Ethics and Economics An Introduction to Free Markets, Equality and Happiness - Graafland, Johan (Taylor & Francis, 2022)
This textbook applies economic ethics to evaluate the free market system and enables students to examine the impact of free markets using the three main ethical approaches: utilitarianism, principle-based ethics and virtue ethics. Ethics and Economics systematically links empirical research to these ethical questions, with a focus on the core topics of happiness, inequality and virtues. Each chapter offers a recommended further reading list. The final chapter provides a practical method for applying the different ethical approaches to morally evaluate an economic policy proposal and an example of the methodology being applied to a real-life policy. This book will give students a clear theoretical and methodological toolkit for analyzing the ethics of market policies, making it a valuable resource for courses on economic ethics and economic philosophy. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non-Commercial (CC-BY-NC) 4.0 license.